2009
DOI: 10.3390/ijms10083531
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Probiotics in the Poultry Industry

Abstract: The increase of productivity in the poultry industry has been accompanied by various impacts, including emergence of a large variety of pathogens and bacterial resistance. These impacts are in part due to the indiscriminate use of chemotherapeutic agents as a result of management practices in rearing cycles. This review provides a summary of the use of probiotics for prevention of bacterial diseases in poultry, as well as demonstrating the potential role of probiotics in the growth performance and immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
340
0
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(365 citation statements)
references
References 83 publications
11
340
0
14
Order By: Relevance
“…In our study, prebiotictreated chickens show trend for increased FCR. It has been suggested that the effect of prebiotics on chicken growth performance, could be related to metabolism modification linked to an increase in the digestive enzymes activity (Pruszynska-Oszmalek et al, 2015), the decrease in bacterial enzymes activity and ammonia production along with the improved FI and digestion (Kabir, 2009). Our results indicate a positive stimulation of the broiler BW expressed as soon as in the starter period (1 to 21 days), which might be explained by early supplementation of chicken embryos with prebiotics using in ovo method.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, prebiotictreated chickens show trend for increased FCR. It has been suggested that the effect of prebiotics on chicken growth performance, could be related to metabolism modification linked to an increase in the digestive enzymes activity (Pruszynska-Oszmalek et al, 2015), the decrease in bacterial enzymes activity and ammonia production along with the improved FI and digestion (Kabir, 2009). Our results indicate a positive stimulation of the broiler BW expressed as soon as in the starter period (1 to 21 days), which might be explained by early supplementation of chicken embryos with prebiotics using in ovo method.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are beneficial live microorganisms primarily including various species of bacteria and fungi (Duc et al 2004;Lutful Kabir 2009). Probiotics influence the host organisms' health by maintaining the normal intestinal microbiota, preventing the growth of pathogenic microorganisms, promoting digestion and intake of feed, and inducing the immune system (Kim et al 2009;Lutful Kabir 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics influence the host organisms' health by maintaining the normal intestinal microbiota, preventing the growth of pathogenic microorganisms, promoting digestion and intake of feed, and inducing the immune system (Kim et al 2009;Lutful Kabir 2009). As such, the use of probiotics on livestock enhances the growth of animals, improves efficiency of feed conversion, and decreases the rate of mortality (Kim et al 2009;Lutful Kabir 2009). Probiotic microorganisms should ideally be non-pathogenic and nontoxic, improve growth of the host animal, and be stable and active during processing and storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, probiotics showing statistically significant and reproducible positive effects in clinical [13] or other large-scale trials [14,15] should keep their well-deserved and earned name. Furthermore, while the society's primary concern is focused at the use of probiotics for various human benefits, the issue is similarly important when it concerns animals of agricultural importance [16], aquacultures [17], and poultry [18].…”
mentioning
confidence: 99%